2020
DOI: 10.1002/asjc.2311
|View full text |Cite
|
Sign up to set email alerts
|

Event‐triggered stabilization for continuous‐time saturating Markov jump systems with generally uncertain transition rates

Abstract: This paper is concerned with the stabilization for continuous‐time saturating Markov jump system with generally uncertain transition rates (GUTRs) under event‐triggered strategy. In the GUTRs model, the transition rate could be unknown or only its estimated value and estimated error bound are known. In practical systems, actuator saturation commonly exists, which may lead to instability. Event‐triggered strategy is introduced in Markov jump systems to save communication resources. A stochastic stabilization co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Unlike the conventional time-triggered control approach where the control signal is updated periodically, the ETC approach is aperiodic. The control signal is updated in the ETC approach based on a predefined triggering instant [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the conventional time-triggered control approach where the control signal is updated periodically, the ETC approach is aperiodic. The control signal is updated in the ETC approach based on a predefined triggering instant [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is desirable to design an effective control scheme that reduces the communication and computational burden between nodes without any loss in control accuracy. Many approaches have been successfully adopted to minimize the amount of communication between the components [2–4]. The event‐triggered control (ETC) approach is the recent and ongoing trend to reduce the communication between the network components and save channel bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lateral stability control is very important for the IEV-DFIM. Many researchers have studied the traditional engine vehicle lateral stability control methods and got lots of achievements such as H ∞ control method [15][16][17][18][19][20], sliding mode control method [21][22][23], optimal control method [24], nonlinear model predictive control method [25], neural networks optimal control method [26], fuzzy control method [27], and other methods [28][29][30]. There are also some achievements for EV in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Some typical engineering applications of MJLSs can be found in the wind turbine and networked control system [3][4][5]. Meanwhile, some existing results on study-ing the stability analysis and control/filtering issues of MJLSs have been reported in several studies [6][7][8][9][10][11] and the references therein.…”
Section: Introductionmentioning
confidence: 99%